PLA2G6 Mutations Related to Distinct Phenotypes: A New Case with Early-onset Parkinsonism. (16th March 2016) - Giri, Anamika; Guven, Gamze; Hanagasi, Hasmet; Hauser, Ann-Kathrin; Erginul-Unaltuna, Nihan; Bilgic, Basar; Gurvit, Hakan; Heutink, Peter; Gasser, Thomas; Lohmann, Ebba; Simón-Sánchez, Javier
Background: PLA2G6 -associated neurodegeneration (PLAN) is a recessive neurodegenerative disorder characterized by three distinct phenotypes: infantile neuroaxonal dystrophy (INAD), atypical neuroaxonal dystrophy (atypical NAD), and PLA2G6 -related dystonia–parkinsonism. Methods: A consanguineous index case from Turkey was diagnosed with early-onset Parkinsonism at the Istanbul Faculty of Medicine. She and her unaffected brother were subjected to whole-genome sequencing. Results: In this report, we describe a 33-year-old index case with parental consanguinity and early-onset Parkinsonism. Whole-genome sequencing of this individual revealed that a homozygous p.R747W mutation in PLA2G6 segregates with the disease in this family Discussion: This result supports the importance of prioritizing this gene in mutational analysis of autosomal recessive Parkinsonism, and confirms the clinical heterogeneity of PLAN.